Environment-friendly cement based on carbonaceous coal gangue and manufacturing method thereof

By activating and surface treatment of coal gangue powder and preparing environmentally friendly cement with other materials, the problem of coal gangue failure to be effectively utilized is solved, and the effect of efficient utilization and environmental protection is achieved, while improving the performance and economic benefits of cement.

CN119461969AActive Publication Date: 2025-02-18CHANGAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411611320.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing technology fails to effectively utilize the active substances in coal gangue, and may cause harmful substances such as heavy metals and sulfides to pollute the environment and cause ecological damage.

Method used

Modified gangue powder was prepared by calcining and surface treatment with β-alanine aqueous solution, combining cement clinker, slag powder, desulfurization gypsum, tourmaline, ammonium sulfate powder and carboxymethylcellulose Sodium, produces environmentally friendly cement based on carbonaceous coal gangue.

Benefits of technology

It realizes efficient utilization of coal gangue, reduces dependence on natural resources, reduces the pollution of solid waste to the environment, improves the gelling characteristics and strength properties of cement, improves construction performance, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130965700000071
    Figure BDA0005130965700000071
Patent Text Reader

Abstract

The invention relates to the field of cement, and particularly discloses environment-friendly cement based on carbonaceous coal gangue and a manufacturing method of the environment-friendly cement. The environment-friendly cement based on carbonaceous coal gangue comprises the following raw materials: 60-80 parts of modified coal gangue powder; 30 to 40 parts of cement clinker; 10 to 20 parts of slag powder; 10 to 15 parts of desulfurized gypsum; 5-10 parts of tourmaline powder; 5-10 parts of ammonium sulfate micro powder; 3 to 7 parts of sodium carboxymethyl cellulose; the modified coal gangue powder is obtained by calcining and activating coal gangue powder and enhancing the coal gangue powder with a beta-alanine aqueous solution. According to the environment-friendly cement, the coal gangue is used as one of the main raw materials, and the coal gangue is converted into the environment-friendly cement with high additional value through activation and enhancement treatment. Not only is the dependence on natural resources reduced, but also the recycling of waste resources is realized, and the resource utilization rate is increased; moreover, the cement disclosed by the invention can keep relatively good working performance in a construction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of cement, and more specifically, to an environmentally friendly cement based on carbonaceous coal gangue and a method for manufacturing the same. Background Art

[0002] Coal gangue is solid waste discharged during coal mining and coal washing. It is a kind of black-gray rock with low carbon content and harder than coal that accompanies coal seams during the coal formation process. It mainly includes excavation gangue during tunnel excavation, gangue mined from the roof, floor and interlayer during mining, and washed gangue picked out during coal washing. The main components of coal gangue are Al2O3 and SiO2. It also contains varying amounts of Fe2O3, CaO, MgO, Na2O, K2O, P2O5, SO3 and trace rare elements (gallium, vanadium, titanium, cobalt).

[0003] In the related art, the harmless treatment of coal gangue is mainly used for roadbed filling, and the coal gangue is used for filling the roadbed to improve the stability and bearing capacity of the roadbed. However, the above treatment scheme is essentially to pile up the coal gangue, and the active substances in the coal gangue are still not effectively utilized. In addition, the heavy metals and sulfides in the coal gangue may seep into the ground, pollute the groundwater and soil, and cause damage to the ecological environment. Summary of the invention

[0004] In order to facilitate the rational and efficient utilization of coal gangue, the present application provides an environmentally friendly cement based on carbonaceous coal gangue and a method for manufacturing the same.

[0005] The environmentally friendly cement based on carbonaceous coal gangue provided in this application adopts the following technical solution: Environmentally friendly cement based on carbonaceous coal gangue includes the following raw materials in parts by weight: 60-80 parts of modified coal gangue powder; 30-40 parts of cement clinker; 10-20 parts of slag powder; 10-15 parts of desulfurized gypsum; Tourmaline powder 5-10 parts; 5-10 parts of ammonium sulfate powder; 3-7 parts of sodium carboxymethyl cellulose; The modified coal gangue powder is obtained by calcining and activating the coal gangue powder and strengthening it with a beta-alanine aqueous solution.

[0006] By adopting the above technical scheme, by using modified coal gangue powder and cement clinker as the main cementitious materials, the synergistic effect of modified coal gangue powder and cement clinker can ensure that cement has good cementing properties and strength properties, and slag powder as a filling material can improve the density of cement material. Desulfurized gypsum is used to adjust the setting time of cement, so that the cement clinker can fully undergo hydration reaction and exert its gelling effect. Adding ammonium sulfate powder helps to improve the early strength of cement, thereby maintaining good working performance. The purpose of adding tourmaline powder is to utilize its good thermoelectric effect. When cement hydration releases heat, tourmaline powder produces a large amount of negative ions due to temperature changes. Negative ions migrate between slurries, which can take away the heat inside the slurry in time, thereby reducing the hydration heat inside the slurry, while ensuring that the temperature inside the cement slurry is uniform, and improving the problem of easy cracking during the cement hardening process. By adding sodium carboxymethyl cellulose, the consistency of the slurry can be increased to make it have good water retention properties, thereby improving the construction performance of cement concrete. This application uses coal gangue as one of the main raw materials and converts it into high-value-added environmentally friendly cement through activation and enhancement treatment, which not only reduces dependence on natural resources, but also realizes the reuse of waste resources and improves resource utilization.

[0007] Optionally, the modified coal gangue powder is obtained by the following method: S1. calcining the coal gangue powder at 600-650° C. for 2-2.5 h to obtain activated coal gangue powder; S2. Mixing activated coal gangue powder and β-alanine aqueous solution, wherein the mass ratio of activated coal gangue powder to β-alanine is 1:3-5, stirring and reacting for 2-2.5 hours, filtering after the reaction, drying and ball-milling the filter residue to obtain modified coal gangue powder.

[0008] By adopting the above technical solution, coal gangue powder can be calcined at a high temperature of 600-650°C, which can cause thermal decomposition and lattice reconstruction, increase surface active sites, and improve reaction activity. β-Alanine can react chemically with the surface functional groups of activated coal gangue powder, improve the surface properties of coal gangue powder, and increase its compatibility and binding ability with other components of cement. The filtration and drying steps can remove unreacted β-Alanine and other impurities to ensure the purity and quality of the modified coal gangue powder. The cement obtained by mixing the modified coal gangue prepared by the above method as a mixed material with cement clinker has good gelling properties and mechanical properties.

[0009] Optionally, the mass concentration of the β-alanine aqueous solution in S2 is 12-15%.

[0010] By adopting the above technical solution, the mass concentration of the β-alanine aqueous solution has a direct impact on the surface activity and reaction characteristics of the activated coal gangue powder. When the concentration is too low, the reaction is insufficient, which may lead to poor modification effect; when the concentration is too high, it may cause waste and increase production costs. Therefore, choosing the appropriate concentration of the β-alanine aqueous solution can reduce production costs and improve product quality while ensuring the reaction effect.

[0011] Optionally, the tourmaline powder is preferably magnesium tourmaline powder.

[0012] By adopting the above technical solution, the magnesium tourmaline powder has a more significant thermoelectric effect due to the presence of metal ions, thereby having a better heat conduction effect, and can reduce the problem of cement cracking caused by cement hydration heat release.

[0013] Optionally, the particle size of the magnesium tourmaline powder is 100-300 mesh.

[0014] Optionally, the particle size of the ammonium sulfate powder is 100-300 mesh.

[0015] By adopting the above technical solution, the particle sizes of tourmaline powder and ammonium sulfate powder are controlled within the above range, which helps to improve the reactivity and mixing uniformity of the materials, thereby improving the performance of cement.

[0016] Optionally, the raw materials further include 3-5 parts of methacryloxysilane.

[0017] By adopting the above technical solution, the addition of silane coupling agents such as methacryloxysilane contains unsaturated double bonds, which can react with the hydroxyl groups on the surface of tourmaline powder to form stable chemical bonds, thereby enhancing the interfacial bonding force between the tourmaline powder and the cement matrix, making the internal particles of the cement more tightly combined, reducing internal microcracks and pores, and thus improving the overall strength of the cement.

[0018] In a second aspect, the present application provides a method for producing environmentally friendly cement based on carbonaceous coal gangue, using the following technical solution: The method for producing environmentally friendly cement based on carbonaceous coal gangue comprises the following steps: (1) Batching: Weigh all raw materials according to the proportion, put the raw materials except cement clinker into a blender and stir them to make them uniform; (2) Adding water: Add 150-200 parts of water into the blender and continue to blend until a uniform slurry is formed; (3) Drying: The slurry is dried at a temperature of 60-80°C for 24-48 hours. The dried slurry is ball-milled and mixed evenly with cement clinker and then packaged to obtain a finished product.

[0019] By adopting the above technical scheme, the production process of the environmentally friendly cement is simple, the production cost is low, and it has good economic benefits. At the same time, it can make efficient and reasonable use of solid waste resources such as coal gangue and slag, effectively reducing the damage caused by large amounts of solid waste to the ecological environment.

[0020] In summary, this application has the following beneficial effects: 1. Since the present application adopts modified coal gangue powder and cement clinker as the main cementitious materials, the synergistic effect of modified coal gangue powder and cement clinker can ensure that the cement has good cementitious properties and strength performance. Coal gangue is used as one of the main raw materials, and it is converted into high-value-added environmentally friendly cement through activation and enhancement treatment. This not only reduces the dependence on natural resources, but also realizes the reuse of waste resources and improves resource utilization. By adding tourmaline powder, since tourmaline powder has a good thermoelectric effect, when cement hydration releases heat, tourmaline powder produces a large amount of negative ions due to temperature changes, and the negative ions are free and displaced between the slurry, so that the heat inside the slurry can be transferred and taken away in time, thereby reducing the hydration heat inside the slurry, and at the same time promoting the uniform temperature inside the cement slurry, thereby improving the problem of easy cracking of cement hardening.

[0021] 2. In this application, the gangue powder is activated at high temperature, and then surface treated with a β-alanine aqueous solution. The gangue powder is calcined at a high temperature of 600-650°C, which can cause thermal decomposition and lattice reconstruction, increase surface active sites, and improve reaction activity. β-alanine reacts chemically with the functional groups on the surface of the activated gangue powder to form chemical bonds, thereby improving the surface properties of the gangue powder. This increases its compatibility and binding ability with other components of cement, thereby improving the gelling properties and strength properties of cement.

[0022] 3. The method of the present application has a simple production process, low production cost, and good economic benefits. At the same time, it can efficiently and reasonably utilize solid waste resources such as coal gangue and slag, effectively reducing the damage caused by large amounts of solid waste to the ecological environment. DETAILED DESCRIPTION

[0023] The present application is further described in detail below in conjunction with embodiments.

[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0025] The loose bulk density of the coal gangue powder selected in this application is 1200-1400kg / m3, and the crushing value is 10.0%; the cement clinker for 52.5 grade PI type silicate cement is purchased from Shandong Sanyi New Materials Co., Ltd.; the slag powder is purchased from Lingshou County Zhanxing Mineral Products Co., Ltd., item number 8828; the desulfurized gypsum is purchased from Zaozhuang Xinghao New Materials Co., Ltd., model 653; and the magnesium tourmaline powder is purchased from Lingshou County Yuanda Mica Factory, item number 0067-16.

[0026] Preparation example of modified coal gangue powder Preparation Example 1 S1. calcining the coal gangue powder at 600° C. for 2.5 h to obtain activated coal gangue powder; S2. Take 30 kg of β-alanine and dissolve it in water to prepare a β-alanine aqueous solution with a mass concentration of 12%, mix it with 10 kg of activated coal gangue powder, stir and react for 2 hours, filter after the reaction, dry the filter residue, and ball-mill to obtain modified coal gangue powder.

[0027] Preparation Example 2 S1. calcining the coal gangue powder at 630° C. for 2.5 h to obtain activated coal gangue powder; S2. Take 40 kg of β-alanine and dissolve it in water to prepare a β-alanine aqueous solution with a mass concentration of 13%, mix it with 10 kg of activated coal gangue powder, stir and react for 2.5 hours, filter after the reaction, dry the filter residue, and ball-mill to obtain modified coal gangue powder.

[0028] Preparation Example 3 S1. calcining the coal gangue powder at 650° C. for 2.5 h to obtain activated coal gangue powder; S2. Take 50 kg of β-alanine and dissolve it in water to prepare a β-alanine aqueous solution with a mass concentration of 15%, mix it with 10 kg of activated coal gangue powder, stir and react for 2.5 hours, filter after the reaction, dry the filter residue, and ball-mill to obtain modified coal gangue powder.

[0029] Preparation Example 4 S1. calcining the coal gangue powder at 650° C. for 2.5 h to obtain activated coal gangue powder; S2. Take 50 kg of β-alanine and dissolve it in water to prepare a β-alanine aqueous solution with a mass concentration of 30%, mix it with 10 kg of activated coal gangue powder, stir and react for 2.5 hours, filter after the reaction, dry the filter residue, and ball-mill to obtain modified coal gangue powder.

[0030] Preparation Example 5 S1. calcining the coal gangue powder at 650° C. for 2.5 h to obtain activated coal gangue powder; S2. Take 50 kg of β-alanine and dissolve it in water to prepare a β-alanine aqueous solution with a mass concentration of 5%, mix it with 10 kg of activated coal gangue powder, stir and react for 2.5 hours, filter after the reaction, dry the filter residue, and ball-mill to obtain modified coal gangue powder. Example

[0031] Example 1 The environmentally friendly cement based on carbonaceous coal gangue, its raw material components and dosage are shown in Table 1, wherein the modified coal gangue powder is the modified coal gangue powder prepared in Preparation Example 1, the tourmaline powder is magnesium tourmaline powder, the particle size of the magnesium tourmaline powder is 100 mesh, and the particle size of the ammonium sulfate micropowder is 100 mesh.

[0032] Environmentally friendly cement based on carbonaceous coal gangue is prepared by the following method: (1) Batching: Weigh all raw materials according to the proportion, put all raw materials except cement clinker into a blender and stir them to make them uniform; (2) Adding water: Add 150 kg of water into the stirrer and continue stirring to form a uniform slurry; (3) Drying: The slurry is dried at a temperature of 60° C. for 48 hours. The dried slurry is ball-milled and mixed evenly with cement clinker and then packaged to obtain a finished product.

[0033] Example 2 The environmentally friendly cement based on carbonaceous coal gangue, its raw material components and dosage are shown in Table 1, wherein the modified coal gangue powder is the modified coal gangue powder prepared in Preparation Example 2, the tourmaline powder is magnesium tourmaline powder, the particle size of the magnesium tourmaline powder is 200 mesh, and the particle size of the ammonium sulfate micropowder is 200 mesh.

[0034] Environmentally friendly cement based on carbonaceous coal gangue is prepared by the following method: (1) Batching: Weigh all raw materials according to the proportion, put all raw materials except cement clinker into a blender and stir them to make them uniform; (2) Adding water: Add 170 kg of water into the stirrer and continue stirring to form a uniform slurry; (3) Drying: The slurry is dried at a temperature of 70° C. for 36 hours. The dried slurry is ball-milled and mixed evenly with cement clinker and then packaged to obtain a finished product.

[0035] Example 3 The environmentally friendly cement based on carbonaceous coal gangue, its raw material components and dosage are shown in Table 1, wherein the modified coal gangue powder is the modified coal gangue powder prepared in Preparation Example 3, the tourmaline powder is magnesium tourmaline powder, the particle size of the magnesium tourmaline powder is 300 mesh, and the particle size of the ammonium sulfate micropowder is 300 mesh.

[0036] Environmentally friendly cement based on carbonaceous coal gangue is prepared by the following method: (1) Batching: Weigh all raw materials according to the proportion, put all raw materials except cement clinker into a blender and stir them to make them uniform; (2) Adding water: Add 200 kg of water into the stirrer and continue stirring to form a uniform slurry; (3) Drying: The slurry is dried at a temperature of 80° C. for 24 hours. The dried slurry is ball-milled and mixed evenly with cement clinker and then packaged to obtain a finished product.

[0037] Table 1 Raw material components and dosage of cement in Examples 1-3 (kg) Example 1 Example 2 Example 3 Modified coal gangue powder 60 70 80 Cement clinker 40 30 20 Slag powder 10 15 20 Desulfurization gypsum 10 13 15 Magnesium tourmaline powder 5 8 10 Ammonium sulfate powder 5 7 10 Sodium Carboxymethyl Cellulose 3 5 7 Example 4 The environmentally friendly cement based on carbonaceous coal gangue is different from that in Example 3 in that the modified coal gangue powder in the raw material of this embodiment is the modified coal gangue powder prepared in Preparation Example 4.

[0038] Example 5 The environmentally friendly cement based on carbonaceous coal gangue is different from that in Example 3 in that the modified coal gangue powder in the raw materials of this embodiment is the modified coal gangue powder prepared in Preparation Example 5.

[0039] Example 6 The environmentally friendly cement based on carbonaceous coal gangue is different from that in Example 3 in that the tourmaline powder in the raw material of this example is lithium tourmaline powder.

[0040] Example 7 The environmentally friendly cement based on carbonaceous coal gangue is different from that in Example 3 in that 3 kg of methacryloxypropyltrimethoxysilane is further added to the raw materials in this example.

[0041] Example 8 The environmentally friendly cement based on carbonaceous coal gangue is different from that in Example 3 in that 5 kg of methacryloxypropyltrimethoxysilane is further added to the raw materials in this example.

[0042] Comparative Example Comparative Example 1 The environmentally friendly cement based on carbonaceous coal gangue is different from Example 3 in that an equal amount of cement clinker is used in this comparative example to replace the modified coal gangue powder.

[0043] Comparative Example 2 The environmentally friendly cement based on carbonaceous coal gangue is different from Example 3 in that an equal amount of unmodified coal gangue powder is used in the raw materials of this comparative example instead of the modified coal gangue powder.

[0044] Comparative Example 3 The environmentally friendly cement based on carbonaceous coal gangue is different from that in Example 3 in that an equal amount of cement clinker is used in the raw materials of this comparative example instead of magnesia tourmaline powder.

[0045] Performance testing Detection method / test method The cement prepared in Examples 1-8 and Comparative Examples 1-3 was used as the test sample. The standard consistency water consumption, setting time and stability were measured according to the method of GB / T1346-2001. The mortar strength was measured according to GB / T17671-1999. The results are shown in Table 2.

[0046] Table 2 Test results of Examples 1-6 and Comparative Examples 1-4 It can be seen from Examples 1-3 and Comparative Example 1 and Table 2 that in this embodiment, modified coal gangue is used to replace a portion of cement clinker, and the stability of the cement finally prepared is qualified, the setting time also meets the cement design requirements, and compared with the cement made entirely of cement clinker, its flexural strength and compressive strength are better maintained. Therefore, the modified coal gangue powder of the present application can exert better gelling properties and strength performance.

[0047] In combination with Examples 3-5 and Table 2, it can be seen that the concentration of the β-alanine aqueous solution when preparing modified coal gangue has an important influence on the performance of the modified coal gangue powder, and thus has a great influence on the compressive strength of cement. The mass concentration of the β-alanine aqueous solution provided in this application is 12-15%, which can enable the cement to maintain good compressive strength after the coal gangue powder is modified.

[0048] Combining Example 3 with Examples 7-8 and Table 2, it can be seen that the addition of methacryloxy silane to the raw materials can react with the hydroxyl groups on the surface of the tourmaline powder to form a stable chemical bond, thereby improving the interfacial bonding force between the tourmaline powder and the cement matrix, thereby improving the overall strength of the cement.

[0049] Combining Examples 3 and 6 and Table 2, it can be seen that the compressive strength of the cement finally prepared by using lithium tourmaline powder as the raw material is lower than that of magnesium tourmaline powder.

[0050] Combining Example 3 and Comparative Example 2, and combining with Table 2, it can be seen that the strength of the cement mortar prepared by using unmodified coal gangue powder compared with that prepared by using modified coal gangue powder has different degrees of loss, indicating that the use of modified coal gangue has a good promoting effect on maintaining the performance of cement.

[0051] Combining Example 3 and Comparative Example 3, and combining with Table 2, it can be seen that in Comparative Example 3, since magnesium tourmaline powder is not used, although the flexural strength of the prepared cement mortar is not greatly lost, it has a greater impact on the compressive strength, ultimately resulting in a greater loss in compressive strength.

[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. Environmentally friendly cement based on carbonaceous coal gangue, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of modified coal gangue powder; 30-40 parts of cement clinker; 10-20 parts of slag powder; 10-15 parts of desulfurized gypsum; Tourmaline powder 5-10 parts; 5-10 parts of ammonium sulfate powder; 3-7 parts of sodium carboxymethyl cellulose; The modified coal gangue powder is obtained by calcining and activating the coal gangue powder and strengthening it with a beta-alanine aqueous solution.

2. The environmentally friendly cement based on carbonaceous coal gangue according to claim 1, characterized in that: The modified coal gangue powder is obtained by the following method: S1. calcining the coal gangue powder at 600-650° C. for 2-2.5 h to obtain activated coal gangue powder; S2. Mixing activated coal gangue powder and β-alanine aqueous solution, wherein the mass ratio of activated coal gangue powder to β-alanine is 1:3-5, stirring and reacting for 2-2.5 hours, filtering after the reaction, drying and ball-milling the filter residue to obtain modified coal gangue powder.

3. The environmentally friendly cement based on carbonaceous coal gangue according to claim 2, characterized in that: The mass concentration of the β-alanine aqueous solution in S2 is 12-15%.

4. The environmentally friendly cement based on carbonaceous coal gangue according to claim 1, characterized in that: The tourmaline powder is magnesium tourmaline powder.

5. The environmentally friendly cement based on carbonaceous coal gangue according to claim 4, characterized in that: The particle size of the magnesium tourmaline powder is 100-300 meshes.

6. The environmentally friendly cement based on carbonaceous coal gangue according to claim 1, characterized in that: The particle size of the ammonium sulfate micropowder is 100-300 meshes.

7. The environmentally friendly cement based on carbonaceous coal gangue according to claim 1, characterized in that: The raw materials also include 3-5 parts of methacryloxy silane.

8. The method for producing environmentally friendly cement based on carbonaceous coal gangue according to any one of claims 1 to 7, characterized in that: The steps include: (1) Batching: Weigh all raw materials according to the proportion, put the raw materials except cement clinker into the mixer and stir them to make them evenly mixed; (2) Adding water: Add 150-200 parts of water into the blender and continue to blend until a uniform slurry is formed; (3) Drying: Dry the slurry at a temperature of 60-80°C for 24-48 hours. After ball milling, mix the dried slurry with cement clinker and package it to obtain the finished product.

Citation Information

Patent Citations

  • Cement containing biomass combustion waste materials and preparation method thereof

    CN115043637A

  • Low-carbon cementing material and preparation method thereof

    CN116874210A

  • Low-carbon concrete for regulating strength by replacing cement with coal gangue and preparation method of low-carbon concrete

    CN118005358A

  • Inorganic cementing material, foam concrete and preparation method thereof

    CN118324552A